2012
DOI: 10.1007/s11606-012-2058-9
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Outcomes for Minority Adults with Asthma: A Systematic Review

Abstract: OBJECTIVES:To systematically review the literature to characterize interventions with potential to improve outcomes for minority patients with asthma. DATA SOURCES: Medline, PsycINFO, CINAHL, Cochrane Trial Databases, expert review, reference review, meeting abstracts. STUDY ELIGIBILITY CRITERIA, PARTICIPANTS, AND INTEVENTIONS: Medical Subject Heading (MeSH) terms related to asthma were combined with terms to identify intervention studies focused on minority populations. Inclusion criteria: adult population; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…[2][3][4][5][6] While many valuable ideas to address racial and ethnic health disparities are being pursued outside of the healthcare system, Finding Answers focuses specifically on what can be accomplished once regular access to healthcare services is achieved. Thus, the reviews focused on interventions that occur in or have a sustained linkage to a healthcare delivery setting; programs that were strictly communitybased were outside the scope of the project.…”
Section: Findings From the Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6] While many valuable ideas to address racial and ethnic health disparities are being pursued outside of the healthcare system, Finding Answers focuses specifically on what can be accomplished once regular access to healthcare services is achieved. Thus, the reviews focused on interventions that occur in or have a sustained linkage to a healthcare delivery setting; programs that were strictly communitybased were outside the scope of the project.…”
Section: Findings From the Systematic Reviewsmentioning
confidence: 99%
“…The asthma paper found that educational interventions were most common, with culturally tailored, skills-based education showing promise. 5 Outpatient support, as well as education for inpatient and emergency department patients, were effective. Similarly, the HIV review noted that interactive, skills-based instruction was more likely to be effective than didactic educational approaches for changing sexual health behavior.…”
Section: Findings From the Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the few culturally specific interventions for asthma tested in randomised trials,[9–18] only one (a negative study set in the UK) has targeted south Asians. [15] Most have been set in the USA and directed at African American or Hispanic populations, with inconsistent improvements in quality of life[12, 17, 19] and health care use.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a chronic, costly, and often debilitating medical condition that affects more than 25 million people in the US 1 and results in significant healthcare utilization: over 10 million outpatient appointments 2 , 1.5 million emergency department visits, and 400,000 hospitalizations 3 , costing over $30 billion 4 annually. It is well-described that worse health outcomes are seen in low-income and minority patients.…”
Section: Introductionmentioning
confidence: 99%